Safety and Efficacy of Stereotactic Arrhythmia Radioablation for the Treatment of Ventricular Tachycardia: A Systematic Review - Volpato, Giovanni; Compagnucci, Paolo; Cipolletta, Laura; Parisi, Quintino; Valeri, Yari; Carboni, Laura; Giovagnoni, Andrea; Dello Russo, Antonio; Casella, Michela (Frontiers in Cardiovascular Medicine, 2022)
Catheter ablation (CA) is a fundamental therapeutic option for the treatment of recurrent ventricular arrhythmias. Notwithstanding the tremendous improvements in the available technology and the increasing amount of evidence in support of CA, in some patients the procedure fails, or is absolutely contraindicated due to technical or clinical issues. In these cases, the clinical management of patients is highly challenging, and mainly involves antiarrhythmic drugs escalation. Over the last 5 years, stereotactic arrhythmia radioablation (STAR) has been introduced into clinical practice, with several small studies reporting favorable arrhythmia-free outcomes, without severe side effects at a short to mid-term follow-up. In the present systematic review, we provide an overview of the available studies on stereotactic arrhythmia radioablation, by describing the potential indications and technical aspects of this promising therapy.